Systematic review of patient-reported outcome measures for opioid use disorder recovery - Pytell, Jarratt D.; Pales, Dennis; Simon, Caty; Beaudoin, Jarett; Ahmed Osman, Ahmed Mohamed Yehia Naguib; Svoboda, Ellie; Christine, Paul J.; Matlock, Daniel; Schwartz, Robert; Binswanger, Ingrid A. (Wiley, 2025)
Background and aims: Recovery-focused measurement-based care of opioid use disorder (OUD) could inform clinical care by assessing patient-reported outcome measures (PROMs). We sought to identify and describe validated PROMs which assess recovery among patients with OUD, focusing on PROM characteristics, recovery domains and pragmatism for implementation in outpatient settings. Methods: A preregistered (PROSPERO: CRD42023394770) systematic review was conducted using the Consensus-based Standards for the selection of health Measurement Instruments (COSMIN) guidelines. Validated PROMs that assessed at least one of 17 recovery domains and contained fewer than 50 items were identified. The review described PROM characteristics, including the number of items, subscales, response options and time to complete. Content validity was assessed from the patient perspective. Recovery domains assessed were categorized into 17 domains, including substancerelated, psychological health and quality of life. The presence of clinically relevant score changes was assessed. Hierarchical clustering was performed to describe co-occurrence patterns among recovery domains. Results: A total of 122 studies were included, identifying 90 unique PROMs. Three PROMs (3%) received a ‘moderate’ grade on content validity. PROMs assessed a median of 4 recovery domains [inter-quartile range (IQR) = 1–7], with substance-related outcomes being most common (51%), followed by psychological health (49%), relationships (41%) and physical health (36%). Nineteen PROMs (21%) contained fewer than 10 items, making them highly pragmatic for clinical use. Fourteen PROMs (16%) assessed 8 or more recovery domains and were categorized as comprehensive. Two (2%) comprehensive PROMs were developed with input from individuals with lived experience of substance use, providing a patient-centered perspective. Five PROMs (6%) defined clinically relevant score changes. Conclusions: There are many patient-reported outcome measures (PROMs) which assess diverse and often broadly defined recovery domains that can be used in recoveryfocused measurement-based care of opioid use disorder; however, few PROMs are brief enough to be pragmatic for clinical use, nearly all lack clinically relevant score changes that could help inform treatment decisions, and few were developed with input from people with lived experience.